Cost-effective flow injection amperometric system with metal nanoparticle loaded carbon nanotube modified screen printed carbon electrode for sensitive determination of hydrogen peroxide - Preeyaporn Reanpang (2018)
© 2015 Elsevier B.V. All rights reserved. Various metal nanoparticles (NPs) decorated on carbon nanotube (CNT) was modified on the home-made screen printed carbon electrode (SPCE) in order to enhances sensitivity of hydrogen peroxide (H2O2) determination. The simple casting method was used for the electrode modification. The monometallic and bimetallic NPs modified electrodes were investigated for their electrochemical properties for H2O2 reduction. The Pd-CNT/SPCE is appropriated to measure the H2O2 reduction at a potential of -0.3 V, then this modified electrode was incorporated with a home-made flow through cell and applied in a simple flow injection amperometry (FI-Amp). Some parameters influencing the resulted modified electrode and the FI-Amp system were studied. The proposed detection system was able to detect H2O2 in the range of 0.1-1.0 mM, with detection limit of 20 μM. Relative standard deviation for 100 replicated injections of 0.6 mM H2O2 was 2.3%. The reproducibility of 6 electrodes preparing in 3 different lots was 8.2%. It was demonstrated for determination of H2O2 in disinfectant, hair colorant and milk samples. Recoveries in the range of 90-109% were observed. The developed system provided high stability, good repeatability, high sample throughput and low reagent consumption.